Menciptakan Pimpinan Yang Handal Dalam Meningkatkan Kinerja Karyawan - Jenita, Jenita (Komunitas Manajemen Kompetitif, 2015)
Abstract: The aim of this paper is to find out how to create reliable leaders in order to improve the employee performance in the organization that he leads. Reliable leaders are the foundation of effective leadership in which their thinking is a based on organization’s task. The role of a leader is very significant to achieve the organization’s task and goals and to improve employee performance, which are the effective and reliable leadership is able to provide guidance to any business activity in order to achieve organizational goals. The leadership style could be a proper guideline in improving employee performance of an organization. Improvement of an employee performance has a positive impact on the organization, and is expected to increase the effectiveness and efficiency of the organization. Either method is to create an effective leader and reliable Keywords: Leaderhip, Performance